2021
DOI: 10.1155/2021/9847714
|View full text |Cite
|
Sign up to set email alerts
|

L-Moments and Calibration-Based Estimators for Variance Parameter

Abstract: The subject of variance estimation is one of the most important topics in statistics. It has been clarified by many different research studies due to its various applications in the human and natural sciences. Different variance estimators are built based on traditional moments that are especially influenced by the existence of extreme values. In this paper, with the presence of extreme values, we proposed some new calibration estimators for variance based on L-moments under double-stratified random sampling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Using the method of pps sampling, many authors like Rao, 1 Tripathi, 2 Anita and Bahl, 3,22 Patel and Bhatt, 4 Ahmad and Shabbir 5 and Singh et al 6 have suggested improved estimators for estimating different population parameters while Anas et al 7,8 and Shahzad et al 9,10 have proposed calibration based mean and variance estimators using L$$ L $$‐moments. In order to examine the properties and efficiency of the proposed estimators in terms of mean square error, some of the well‐established forms of suggested estimators under pps sampling have been adopted in this section and their properties have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Using the method of pps sampling, many authors like Rao, 1 Tripathi, 2 Anita and Bahl, 3,22 Patel and Bhatt, 4 Ahmad and Shabbir 5 and Singh et al 6 have suggested improved estimators for estimating different population parameters while Anas et al 7,8 and Shahzad et al 9,10 have proposed calibration based mean and variance estimators using L$$ L $$‐moments. In order to examine the properties and efficiency of the proposed estimators in terms of mean square error, some of the well‐established forms of suggested estimators under pps sampling have been adopted in this section and their properties have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…L-moments are widely used in applied research such as civil engineering, meteorology, and hydrology. Among the benefits of L-moments include their capacity to work as a linear function of the data, being less prone to sample variability, being more robust to extreme values or outliers in the data and allowing for more confident inferences about the underlying probability distribution from small samples (Anas et al, 2021). This implies that L-moments are less affected by outliers, and the bias of their small sample estimates is kept to a minimum.…”
Section: Introductionmentioning
confidence: 99%